Solve for \( x \) : (a) \( 4.3^{x}+3^{x}=15 \) (c) \( 2^{x+2}+2^{x-2}+2^{x}=84 \) (e) \( 3^{2 x}-2.3^{x+2}+81=0 \) (g) \( 4^{x}+4.2^{x}-5=0 \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Extra Insights
To solve for \( x \) in the given equations, we can use a combination of algebraic manipulations and substitutions. (a) For the equation \( 4.3^{x}+3^{x}=15 \): Let's set \( y = 3^{x} \). Then, we have: \[ 4y + y = 15 \] This simplifies to: \[ 5y = 15 \] So, \( y = 3 \), which means \( 3^{x} = 3 \). Thus, \( x = 1 \). (c) For \( 2^{x+2}+2^{x-2}+2^{x}=84 \): Rewriting this gives: \[ 4 \cdot 2^{x} + \frac{1}{4} \cdot 2^{x} + 2^{x} = 84 \] Combining the terms: \[ (4 + \frac{1}{4} + 1) 2^{x} = 84 \] This simplifies to: \[ \frac{20}{4} + \frac{1}{4} = \frac{21}{4} \cdot 2^{x} = 84 \] So, \[ 2^{x} = \frac{84 \times 4}{21} = 16 \] Thus, \( 2^{x} = 2^{4} \), leading to \( x = 4 \). (e) For \( 3^{2 x}-2.3^{x+2}+81=0 \): Letting \( z = 3^{x} \), we can rewrite the equation as: \[ z^2 - 2 \cdot 9z + 81 = 0 \] Simplifying gives: \[ z^2 - 18z + 81 = 0 \] Factoring: \[ (z - 9)^2 = 0 \] Thus, \( z = 9 \) or \( 3^{x} = 3^{2} \), leading to \( x = 2 \). (g) For \( 4^{x}+4.2^{x}-5=0 \): Recognizing that \( 4^{x} = (2^2)^{x} = 2^{2x} \), we rewrite the equation as: \[ 2^{2x} + 4 \cdot 2^{x} - 5 = 0 \] Let \( u = 2^{x} \), leading to: \[ u^{2} + 4u - 5 = 0 \] Factoring gives: \[ (u + 5)(u - 1) = 0 \] So, \( u = -5 \) (not valid as \( u \) must be positive) or \( u = 1 \), which means \( 2^{x} = 1 \). Thus, \( x = 0 \). The solutions are: (a) \( x = 1 \) (c) \( x = 4 \) (e) \( x = 2 \) (g) \( x = 0 \)